KEBIJAKAN POROS MARITIM DUNIA JOKO WIDODO DAN IMPLIKASI INTERNASIONALNYA - Poltak Partogi Nainggolan (Sekretariat Jenderal DPR RI, 2015)
World Maritime Axis has been launched by President Joko Widodo, and its implementation is being overseen by the Indonesian parliament (DPRRI). Countries from inside and outside of the Southeast Asia region show their own different responses, particularly connected with infrastructure development policy and law enforcement on the field. This essay is part of a comprehensive research report on the Indonesian new government’s policy under Joko Widodo and the responses of other countries toward them, which discloses different reactions, arguments, reasons and responses. The research was conducted in 2015 in provinces of Sumatera, Mollucas, and Papua, whose data gathering is carried out by using library studies, focus group discussions, and in-depth interview with decision makers and experts on maritime sector development. Data analysis applies a qualitative method. Its findings reveal inconsistent responses of foreign countries in giving foreign investments for infrastructure development, and their critical views, and moreover, assertive reactions towards law enforcement in the Indonesian water.